Habit-induced oral lesions in different occupations: A comparative study among people between geographical different places of West Bengal - Tathagata Bhattacharjee; Kasturi Mukherjee; Kailash C. Dash; Somnath Gangopadhyay (Journal of Family Medicine and Primary Care)
Introduction: Like general health, oral health also depends upon their occupational environment and occupational health policies. Workplace exposure to environmental tobacco smoke and its harmful effect is well known. The consumption of tobacco, arecanut, and alcohol is the leading preventable cause for development of oral potentially malignant disorders. Aim: To determine prevalence of habit-induced oral lesions in different occupations in different geographical places of West Bengal and compare among them. Method: A total of 841 people aged 15 years and above were selected from different parts of West Bengal. Face-to-face interview was conducted using a structured questionnaire, and oral cavity examination was done in daylight. Data were summarized, and statistical analysis was done. Statistical Analysis Used: Chi-square test and univariate logistic regression done. Results: The people in armed forces had cancer-causing habits most, and managers had cancer-causing habits least. People in armed forces had cancer-causing habits most, and people with Group-1 occupation/managers had cancer-causing habits least.